Klasifikasi Musik Berdasarkan Genre Menggunakan Metode K-Nearest Neighbor - William Soeparman; I Ketut Gede Suhartana (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
Currently the amount of music in digital form continues to increase rapidly. This causes manual genre labeling of music to be inefficient. Genre labeling can be done automatically using artificial intelligence algorithms. The artificial intelligence algorithm used is an algorithm that can classify music based on genre by using the features contained in the music. This study discusses the classification of music based on genre using the K-Nearest Neighbor method or algorithm and 6 musical features, namely beat, energy, danceability, loudness, liveness, and valence. The accuracy value in this study is 54.3%.